Assessing the applicability of collaborative procurement systems. (16th October 2008) - Lin, Yichen; Yu, Pingwen; Lin, Chaoche
The advent of new technologies in automation, information, and path structures will drive commercial development towards retail chains, maximisation, and strategic alliances between businesses. A case study was used to examine how integration can help a company achieve supply chain maturity and procurement activity and business performance improvements. Supply chain maturity includes emphasised function, inside integration, outside integration, and business cooperation. Procurement management considerations involved determining the proper supplier, quality, time, price, and quantity of the product being purchased. Greater maturity was a facilitator, positively influencing procurement activities. Both supply chain maturity and procurement activities had a significant influence on business performance.